Diet composition and niche breadth of mullet Chelon subviridis (Valenciennes, 1836) and Moolgarda engeli (Bleeker, 1858) in Pabean Bay, Indramayu Subdistrict, West Java Province - Gusti Abi Abi Dzar Al Ghiffary; M. F. Rahardjo; Ahmad Zahid; Charles P. H. Simanjuntak; Aries Asriansyah; Reiza Maulana Aditriawan (Jurnal Iktiologi Indonesia, 2018)
The aims of this research was to identify the diet and composition item as well as niche breadth and niche overlap of mullet in Pabean Bay. Fish sampling was carried out from July to December 2016 using trap nets and gill nets. Data analysis including preponderance index, niche breadth, and niche overlap. Chelon subviridis and Moolgarda engeli are two species of mullet that much found in Pabean Bay. The size of body length C. subviridis observed on ranged of 73,34-185,72 mm with a weight of 8,23-115,50 g and M. engeli ranged of 67,51-160,00 mm with a weight of 6,91-96,70 g. Food menu of mullet consists of three groups, namely perifiton, larvae of marine organism, and detritus. Perifiton from Bacillariophyceae was a main diet, particularly Pleurosigma (35,81) in C. subviridis and Nitzschia (27,89) in M. engeli. Changed in composition of each item of diet occurred on any length size group during the observation. C. subviridis and M. engeli have a wide niche breadth with the value were 5,995 and 5,780. Niche breadth of each length group was different. Information on niche breadth indicated the adaptation of mullet to against the availability of diet in the water. Abstrak Penelitian ini bertujuan untuk mengidentifikasi jenis dan komposisi serta luas dan tumpang tindih relung makanan ikan belanak di Teluk Pabean. Pengambilan contoh ikan dilakukan pada Juli hingga Desember 2016 dengan menggu-nakan alat tangkap sero dan jaring insang. Analisis data meliputi indeks bagian terbesar serta luas dan tumpang tindih relung makanan. Dua jenis ikan belanak, Chelon subviridis dan Moolgarda engeli, merupakan spesies yang banyak ditemukan di Teluk Pabean. Ukuran panjang tubuh C. subviridis yang diamati berkisar 73,34-185,72 mm dengan bobot 8,23-115,50 g dan panjang tubuh M. engeli berkisar 67,51-160,00 mm dengan bobot 6,91-96,70 g. Menu ma-kanan ikan belanak terdiri atas tiga kelompok besar, yaitu perifiton, larva organisme, dan detritus. Perifiton dari kelas Bacillariophyceae menjadi kelompok makanan yang banyak dimanfaatkan, khususnya Pleurosigma (35,81) oleh C. subviridis dan Nitzschia (27,89) oleh M. engeli. Perubahan komposisi jenis makanan terjadi pada setiap kelompok ukuran ikan. C. subviridis dan M. engeli memiliki relung makanan yang luas dengan nilai luas relung berturut-turut 5,995 dan 5,780. Luas relung makanan pada setiap kelompok ukuran ikan berbeda. Informasi mengenai luas relung makanan dapat menunjukkan adaptasi ikan belanak terhadap ketersediaan makanan di perairan.